+0  
 
0
647
2
avatar+4 

wie geht das auf t umformen

 08.03.2016
 #1
avatar+10336 
0

Hallo Dutti!

 

0 = 0.012t^2 * e^(- 0.11t) - 0.25t^2 * e^(-0.5t)

 

0.012t2 * e- 0.11t =  0.25t2 * e-0.5t

0.012t² / 0.25t² = e-0.5t / e-0.11t

0.048 = e(- 0.5t + 0.11t)

ln 0.048 = ln e (- 0.5t + 0.11t)

ln 0.048 = - 0.5t + 0.11t

ln 0.048 = - 0.39 t

t = ln 0.048 / - 0.39

t = - 3.0365542607 / - 0.39

 

t = 7.7863658479

 

Probe:

0.012 * 7.786² * e-0.11 * 7.786 = 0.25 * 7.786² * e-0.5 * 7.786 

0.3089 = 0.3089

q.e.d.

 

Gruß asinus :- )

laugh !

 08.03.2016
bearbeitet von asinus  08.03.2016
bearbeitet von asinus  08.03.2016
 #2
avatar+10336 
0

Die zweite Zeile lautet:

 

0.012t2 * e- 0.11t =  0.25t2 * e-0.5t

asinus  08.03.2016

24 Benutzer online